Profil Pedagogical Content Knowledge Mahasiswa Pendidikan Fisika pada mata Kuliah PPL Berdasarkan kerangka Magnusson - Nur Habib Muhammad Iqbal; Fanni Zulaiha (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
The quality of physics learning is greatly influenced by the teacher's ability to integrate content knowledge and pedagogy. However, many pre-service teachers still face challenges in applying Pedagogical Content Knowledge (PCK), especially in field-based contexts such as the teaching practicum (PPL) course. This study aims to describe the PCK profile of physics education students based on the five components of the Magnusson framework, while also addressing the research gap that has mostly focused on experienced teachers. The study employed a quantitative descriptive approach, involving seven students who were assessed through microteaching observations using an instrument based on PCK indicators. The results show that students scored highest in the components of instructional strategies and curriculum knowledge, while the components related to students’ understanding and assessment received relatively lower scores. These findings highlight the importance of strengthening pedagogical dimensions that focus on student thinking and formative assessment. The study concludes that teacher education curricula should be developed in a more integrative, contextual, and explicit manner to comprehensively build PCK competencies. This research contributes to improving the quality of physics teacher education and informs education policy development rooted in reflective teaching practice Keyword: Pedagogical Content Knowledge, physics education students, microteaching, Magnusson_framework, teaching practicum.